Effect of premature loading on punching resistance of reinforced concrete flat slabs. (June 2020) - Shaaban, Ibrahim G.; Hosni, Ayman H.; Montaser, Wael M.; El-Sayed, Moataz M.
Highlights: At 28 days, BS8110-97 and EC2 provide accurate predictions of punching shear capacity while ACI 3182014 and ECP-2018 equations seemed to be conservative. BS8110 - 97 and EC2 did not predict punching shear experimental results accurately for the test slabs under premature loading. ACI 318 (2014) and ECP-2018 provided more reliable results for early loaded slabs when using the concrete compressive strength at the time of loading in prediction. It is recommended to use the actual compressive strength of concrete at early age in calculating punching resistance of slabs in design phase. Abstract: Premature loading of reinforced concrete flat slabs in multi storey buildings during construction may occur after shuttering removal and loading slabs earlier than usual to meet project time targets. Some case studies showed failure of flat slabs, which were prematurely loaded during the construction process before it reaches its full characteristic strength (at 28 days), which was used in structural design. This research aims to address this problem through experimental testing and design application according to current building codes. Eight specimens with dimensions of 1100 * 1100 mm and a total thickness of 120 mm were experimentally tested to study the effect of concrete age and actual compressive strength at loading on the punching shear capacity of reinforced concrete slabs. All specimens were supported by a square column with dimensions of 150 × 150 mm and loaded at the four corners with a span of 1050 mm. Accelerating admixture was used in three studied specimens to achieve higher concrete compressive strength at early ages compared to their companions of normal concrete without these admixtures. It was found that increasing concrete compressive strength of slab from 25 N / m m 2 to 35 N l m m 2 (40 % increase) for normal concrete, without early admixture, improved punching shear capacity by 26 %, while increasing it to 45 N / m m 2 (80 % increase) improved punching shear capacity by 49 % when the specimens were loaded 7 days after casting. In addition, using an accelerating admixture increased early concrete compressive strength, which improved punching shear capacity of reinforced concrete slab over that without accelerating admixture by 31 % and 29 % after 7 days and 14 days, respectively. According to inclusion of reinforcement ratio, BS8110 - 97 and Eurocode-2004 (EC2) design codes showed the most accurate prediction of punching shear capacity at 28 days, while ACI-2014 and ECP 203-2018 seemed conservative as their equations do not take steel ratio into consideration. At early ages, BS8110 - 97 and Eurocode-2004 (EC2) design equations did not provide accurate prediction of punching shear capacity while ACI and ECP provided reliable equations. It is recommended to use the actual compressive strength of concrete at early age (7 days for example) for calculating punching shear resistance of flat slabs prior to shuttering removal to prevent any premature loading.